Modern trends for peripheral nerve repair and regeneration: beyond the hollow nerve guidance conduit - Carvalho, Cristiana Rodrigues (2019)
Peripheral nerve repair and regeneration remains among the greatest challenges in tissue engineering 29 and regenerative medicine. Even though peripheral nerve injuries (PNIs) are capable of some degree 30 of regeneration, frail recovery is seen even when the best microsurgical technique is applied. PNIs are 31 known to be very incapacitating for the patient, due to the deprivation of motor and sensory abilities. 32 Since there is no optimal solution for tackling this problem up to this day, the evolution in the field is 33 constant, with innovative designs of advanced nerve guidance conduits (NGCs) being reported every 34 day. As a basic concept, a NGC should act as a physical barrier from the external environment, 35 concomitantly acting as physical guidance for the regenerative axons across the gap lesion. NGCs 36 should also be able to retain the naturally released nerve growth factors secreted by the damaged nerve 37 stumps, as well as reducing the invasion of scar tissue-forming fibroblasts to the injury site. Based on 38 the neurobiological knowledge related to the events that succeed after a nerve injury, neuronal 39 subsistence is subjected to the existence of an ideal environment of growth factors, hormones, 40 cytokines, and extracellular matrix (ECM) factors. Therefore, it is known that multifunctional NGCs 41 fabricated through combinatorial approaches are needed to improve the functional and clinical 42 outcomes after PNIs. The present work overviews the current reports dealing with the several features 43 that can be used to improve peripheral nerve regeneration (PNR), ranging from the simple use of hollow 44 NGCs to tissue engineered intraluminal fillers, or to even more advanced strategies, comprising the 45 molecular and gene therapies as well as cell-based therapies.